The Impact of Financial Ratios on Dividend Payouts of “Set50” Listed Companies in the Stock Exchange of Thailand - จะเลินสัก เกมกิลา; จิรอุดมสาโรจน์ พัทธ์ธีรา (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aims to examine the impact of financial ratios on dividend payouts of companies listed in the SET 50 group on the Stock Exchange of Thailand. The analysis covers data from 43 companies across various industries over a period from 2021 to 2023. The financial ratios analyzed include the Current Ratio (CR), Quick Ratio (QR), Debt-to-Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), and Dividend Payout Ratio (DP). The findings revealed that the Return on Assets (ROA), Quick Ratio (QR), and Current Ratio (CR) had a positive impact on dividend payouts at a statistically significant level of 0.05. On the other hand, the Debt-to-Equity Ratio (DER) and Return on Equity (ROE) showed no significant effect on dividend payouts. This research enhances the understanding of the factors influencing corporate decisions on dividend payout policies, which can be valuable for future financial planning and investment strategies.